Гетеропереход на основе кристалла FeIn₂Se₄, полученного методом Бриджмена - Kovalyuk, Z. D.; Katerynchuk, V. M.; Netyaga, V. V.; Zaslonkin, V. A. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
FeIn2Se4 crystals with a layered structure and magnetic component were grown by the Bridgman method. Heterojunctions of type n-InSe–p-FeIn₂Se₄ were fabricated. From the capacitance–voltage characteristics, the potential barrier height of the heterojunctions was determined. Current–voltage characteristics and the temperature dependences of their forward branches were measured, and the diode factor was evaluated. The series resistance of the heterojunctions governs the frequency dependence of the capacitance–voltage characteristics and suppresses the exponential increase of current with voltage. The photoresponse spectrum of the heterojunctions exhibits only a long-wave threshold at 1.25 eV and extends into the ultraviolet region, accompanied by an increase in the quantum efficiency of the photocurrent.